IMPLEMENTASI AKAD IJARAH MUNTAHIYA BITTAMLIK PADA PT. BANK MUAMALAT INDONESIA CABANG PALEMBAN - , Muhammad Dimyati,SH; , Prof. Dr. Abdul Ghofur Anshori, S.H., M.H ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is aims to know the implementation of akad ijarah muntahiya bittamlik in PT. Bank Muamalat Indonesia Palembang branch office and also the mechanism of problem solving that accurs between the customer and PT. Bank Muamalat Indonesia Palembang branch office. This research is an imperical judicial research, that is to research methodic aspect regulations of act and another in use purpose of matter law in Indonesia, with to see reality in field practical. The result of this research show that (1). The Implementation of akad ijarah muntahiya bittamlik in PT Bank Muamalat Indonesia Palembang branch office on technical operational level in field not to the full based on the syariah principle,The meaning there is practicals have been step certainty syariah practical in form akad and application prudential principle, and there is practicals not in step certainty syariah principle that is determining margin, system installment and certainly principle almusawah.( 2). Mechanism problem solving akad ijarah muntahiya bittamlik in PT. Bank Muamalat Indonesia Palembang branch office in pass through 1). Discussion 2). Badan Arbitrase Syariah Nasional ( Basyarnas), 3). The court on local religion judicature. For along this time, PT. Bank Muamalat Indonesia Palembang branch office in problem solving is happen with customer in field priority stripe one that is discussion, for the sake of goodness all of them, but they will also use another if it is necessity